Dermatitis Herpetiformis in Two Patients with Idiopathic Steatorrhoea (Adult Coeliac Disease). Issue 5622 (5th October 1968) - Fraser, N. G.; Ferguson, Anne; Murray, D.
Abstract : Two patients who had had idiopathic steatorrhoea for several years developed typical eruptions of dermatitis herpetiformis. In each case the rash responded to treatment with dapsone. It is more usual for the rash to precede the enteropathy when the two occur together, but the association between coeliac disease and dermatitis herpetiformis is not yet clear.